Retinal rhythms in chicks: circadian variation in melantonin and serotonin N-acetyltransferase activity. - Hamm, H E (1980)
There is a large-amplitude circadian rhythm of indoleamine metabolism in the retina-pigment epithelium of the chicken. N-Acetyltransferase activity (arylamine acetyltransferase; acetyl-CoA:arylamine N-acetyltransferase, EC 2.3.1.5) and melatonin content are 15-fold higher at night than during the day in a cycle of a 4-fold increase during the subjective night. Light at midnight inactivates N-acetyltransferase and lowers melatonin. N-Acetyltransferase activity is found predominantly in the retina. The circadian rhythm of this enzyme activity persists in pinealectomized chicks. Thus the pineal is not responsible for retinal indoleamine rhythms. Retinal and pineal levels of N-acetyltransferase activity behave similarly under several conditions. In the chicken, the eye is a major site of rhythmic indoleamine metabolic activity.